2004
DOI: 10.1177/1043463104046694
|View full text |Cite
|
Sign up to set email alerts
|

State Welfare Spending and Religiosity

Abstract: What accounts for cross-national variation in religiosity as measured by church attendance and non-religious rates? Examining answers from both secularization theory and the religious economy perspective, we assert that cross-national variation in religious participation is a function of government welfare spending and provide a theory that links macro-sociological outcomes with individual rationality. Churches historically have provided social welfare. As governments gradually assume many of these welfare fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(122 citation statements)
references
References 21 publications
9
105
0
8
Order By: Relevance
“…Consistent with Palani (2008) and Rees (2009), we find that there is a significant positive correlation between religiosity and income inequality across a wide spectrum of countries including both advanced and less advanced countries. We next show that there is a negative correlation between religiosity and state welfare spending, thus confirming the findings of Gill and Lundsgaarde (2004) and Scheve and Stasavage (2006). However, we go beyond these studies and show that a negative correlation is also present between religiosity and total government spending as well as between religiosity and government spending excluding spending on welfare.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with Palani (2008) and Rees (2009), we find that there is a significant positive correlation between religiosity and income inequality across a wide spectrum of countries including both advanced and less advanced countries. We next show that there is a negative correlation between religiosity and state welfare spending, thus confirming the findings of Gill and Lundsgaarde (2004) and Scheve and Stasavage (2006). However, we go beyond these studies and show that a negative correlation is also present between religiosity and total government spending as well as between religiosity and government spending excluding spending on welfare.…”
Section: Introductionsupporting
confidence: 67%
“…In order to minimize clutter, we only report in Table 6 the results from the simultaneous estimation of equations for taxes. 13 Results suggest that the negative correlation between belief in afterlife and taxes, government spending, and/or transfers seems to be quite robust to different econometric specifications, even after taking into account the pairwise feedback effects between taxes, transfers, and government spending on the one hand, and income inequality, on the other.…”
Section: Estimation and Resultsmentioning
confidence: 90%
“…3 By the early 20 th century, Muslim religious schools were more prevalent than Hindu religious schools in colonial India. The model therefore predicts that Hindus living in Muslimruled states would have worse educational outcomes because Muslim rulers would spend 2 This insight is consistent with the recent literature suggesting that religious expenditure and public good provision are substitutes (Gill and Lundsgaarde 2004;Hungerman 2005; Hungerman and Gruber 2007), but the mechanism is different; those works suggest that public expenditure crowds out religious expenditure, while our model suggests the reverse. This insight is also consistent with Franck and Rainer (2012), who find that rulers exhibit ethnic favoritism in sub-Saharan Africa, favoritism is an important factor in determining education outcomes, and the presence of favoritism is mitigated when citizens belong primarily to one dominant religion.…”
Section: Introductionsupporting
confidence: 80%
“…We only coded rulers as having no historical tie if the history unambiguously indicated that the founding family was non-local to the state population. 26 Second, we created an indicator variable for states that were reprimanded by the GOI for mis-management of their public finances or if they experienced an intervention by the GOI in their local affairs. Our reading suggests the GOI was more likely to reprimand or intervene in larger and more important states.…”
Section: Datamentioning
confidence: 99%
“…Similarly, Martin (1978) asserts that a theory of secularization need not assume that secularization is either a long-term or an inevitable process. The point is that there are several factors that may affect religiosity, including, among others, religious competition ( Stark and Iannaccone 1994), government welfare spending ( Gill and Lundsgaarde 2004), economic inequality ( Solt, Habel, and Grant 2011), and crime ( Heaton 2007), implying that to the extent that such factors generate a sufficiently strong increase in religiosity among certain individuals, we may observe an increase in aggregate religiosity even if (secondary) education tends to have a negative effect on religiosity. Thus, it can be said that, if secularization is not a continuous and irreversible process, and periods of secularization alternate with periods of religious revival, then the results of this study are consistent with the secularization hypotheses insofar as they suggest (at least for our sample) that permanent changes in secondary education have negative effects on religiosity the long run.…”
Section: Resultsmentioning
confidence: 99%